Pelatihan Penggunaan Sistem Informasi Data Kependudukan Warga Perumahan Puri Cendana Bekasi - Srisulistiowati, Dwi Budi; Fadillah, Irsya; Utomo, Ardhian Sulistyo; Hakiki, Muhammad Ilham; Harumia, Devi; Yasir, Muammar; Hidayat, Muhammad Fahreza (Journal Of Computer Science Contributions (JUCOSCO), 2023)
The development of the citizen management information system (SIMWARGA) at the RT level will be carried outin stages. For initial development, what is considered very important is the processing of citizen data so that itgreatly affects the accuracy of population data globally. This is a challenge for the group of participants in thereal work lecture through a community empowerment program carried out in groups at the Puri Cendana 1Housing location, especially in RW 008. The purpose of this training is to increase knowledge and insight foradministrators, as well as provide training to be able to manage citizen data. The material provided in thistraining is in the form of, Addition of Population Data, Family Card Data, Birth Data, Death Data, Migrant Dataand Move Data, Management awareness in the use of population data applications is expected to reduce datainput errors. The methodology of implementing this activity begins with site preparation and design of informationsystem applications and supporting equipment, literature studies and making training materials. Next is theimplementation. As a result of this training, there was an increase in understanding of the use of the Applicationby 52%. This training also provides new experiences and insights into the use of technology in the populationdata collection process, so that it can improve the quality of RW administrators in managing citizen data. In thefuture, activities like this should continue to be carried out with various kinds of innovations and currenttechnological developments for the development of knowledge in the management in RW.